The Role of Age on Multisensory Bodily Experience: An Experimental Study with a Virtual Reality Full-Body Illusion - Serino, Silvia (Cyberpsychol Behav Soc Netw, 2018)
A growing body of evidence demonstrated that it is feasible to induce ownership over an artificial body to alter bodily experience. However, several uncharted aspects about full-body illusion applications need to be tackled before a complete exploitation of these methods in clinical practice. This work is devoted to explore possible individual age-related differences in shaping changes in body representations induced with a full-body illusion. A total of 40 women were divided into two different age groups according to the median of the variable age. Participants estimated the width of three different body parts (i.e., shoulders, abdomen, and hips) before the entire illusion was induced (baseline), and after the synchronous and the asynchronous conditions. Results revealed that 26-to-55-year-old participants were more resistant to changes induced by the bodily illusion, whereas 19-to-25-year-old participants underestimated their bodies after both conditions. The findings were discussed in terms of the literature exploring age differences in responses to bodily illusion, which could suggest a Bayesian mechanism underlying these individual differences.